Weight Concerns and Eating Attitudes among Romanian Students in Comparison to German Students and Anorexia Nervosa Patients. (13th May 2015) - Joja, O.D.; Nanu, C.; von Wietersheim, J.
Abstract: Epidemiological data in Romania indicate an increase of eating disorders during the last two decades. Weight concerns, disordered eating and some cognitive characteristics were identified as risk factors for developing eating disorders. We investigated 196 Romanian and 110 German female students as well as a group of 31 female anorexia nervosa patients with the Eating Disorders Inventory. The findings might question the patterns of how weight concerns and ineffectiveness may predict eating disorders. Further replication and cross-cultural studies may highlight why and how for Romanian young women being thin appears to be more "normal" than being normal-weight.© 2015 The Authors. Published by Elsevier Ltd.Peer-review under responsibility of the Scientific Committee of PSIWORLD 2014.